2020
DOI: 10.1016/j.micinf.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate mutase affects Stenotrophomonas maltophilia attachment to biotic and abiotic surfaces

Abstract: Stenotrophomonas maltophilia biofilm formation is of increasing medical concern, particularly for lung infections. However, the molecular mechanisms facilitating the biofilm lifestyle in S. maltophilia are poorly understood. We generated and screened a transposon mutant library for mutations that lead to altered biofilm formation compared to wild type. One of these mutations, in the gene for glycolytic enzyme phosphoglycerate mutase (gpmA), resulted in impaired attachment on abiotic and biotic surfaces. As adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…A micro-representation difference analysis (micro-RDA) combined with Northern blotting showed that GPM1 expression increased during biofilm formation by Staphylococcus aureus, when compared with planktonic cultures (Becker et al, 2001), possibly due to oxygen deprivation in biofilm, but also suggesting a potential role of Gpm in bacterial pathogenicity. Although surface exposure of Gpm1 was not confirmed for another opportunistic bacterium -Stenotrophomonas maltophilia -the results obtained for a GPM1-deleted mutant with growth kinetics similar to that of the wild-type showed a reduction in the attachment to CF-derived bronchial epithelial cells, and also to a polystyrene surface (Ramos-Hegazy et al, 2020), suggesting that Gpm1 has a role in the adhesion phenomenon. Similarly, in C. albicans yeast, based on immunodetection analyses, Gpm1 was shown to localize to the cell wall of both, the blastospores and hyphae (Poltermann et al, 2007;Vialás et al, 2012).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…A micro-representation difference analysis (micro-RDA) combined with Northern blotting showed that GPM1 expression increased during biofilm formation by Staphylococcus aureus, when compared with planktonic cultures (Becker et al, 2001), possibly due to oxygen deprivation in biofilm, but also suggesting a potential role of Gpm in bacterial pathogenicity. Although surface exposure of Gpm1 was not confirmed for another opportunistic bacterium -Stenotrophomonas maltophilia -the results obtained for a GPM1-deleted mutant with growth kinetics similar to that of the wild-type showed a reduction in the attachment to CF-derived bronchial epithelial cells, and also to a polystyrene surface (Ramos-Hegazy et al, 2020), suggesting that Gpm1 has a role in the adhesion phenomenon. Similarly, in C. albicans yeast, based on immunodetection analyses, Gpm1 was shown to localize to the cell wall of both, the blastospores and hyphae (Poltermann et al, 2007;Vialás et al, 2012).…”
Section: Introductionmentioning
confidence: 82%
“…In recent years, numerous studies have demonstrated the presence of Gpm in the cell wall of many microorganisms, including such bacteria as S. aureus, Lactobacillus spp. and Stenotrophomonas maltophilia (Becker et al, 2001;Pérez Montoro et al, 2018;Ramos-Hegazy et al, 2020), and yeast-like fungi such as C. parapsilosis, C. tropicalis, C. glabrata and S. cerevisae (Karkowska-Kuleta et al, 2019;Kozik et al, 2015;Motshwene et al, 2003). Nevertheless, the mechanisms of its emergence on the cell surface have not yet been satisfactorily investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial cell wall/membrane is known to be closely related to biofilm formation ( Bucher et al., 2015 ). Additionally, a previous study reported that a phosphoglycerate mutase knockout mutant of Stenotrophomonas maltophilia exhibited a decreased biofilm formation capacity ( Ramos-Hegazy et al., 2020 ). Therefore, we next sought to compare the biofilm formation capacity of Ac (EV) , bdpmAc:Tn (EV), and bdpmAc:Tn (BdpmAc) using a 96-well PVC microplate assay.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes associated with biofilm production in S. maltophilia include those related to LPS production (spgM, rmlC and xanA), fimbriae (smf-1), flagellar biosynthesis (fliA), quorum sensing (ax21), biofilm and swimming motility regulator (bsmR), and the gene for glycolytic enzyme phosphoglycerate mutase (gpmA) [2,14,15,23,24]. Further studies of these specific genes in our strain population should also be conducted to better characterize the genetic mechanisms of biofilm production regulation.…”
Section: Plos Onementioning
confidence: 99%